Perancangan Cloud Storage Menggunakan Freenas Melalui Jalur Tunneling - Sindu Pangestu (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
This paper discusses about the creation of a server for data storage using Freenas operating system, which accesses the server via internet or public IP using a VPN (Virtual Private Network). Data access from the user to the server uses Freenas user authentication and added with VPN user authentication to increase network security and overcome security problems in data transactions such as data theft. The result of the research from the created server, showed that the created VPN path can be used to overcome these security problems. From the data transaction experiments that have been carried out on the server, it shows that the data sent via internet network without a VPN is not encrypted and its contents can still be viewed, while the data using the VPN path has encrypted data and cannot be viewed directly.